2020
DOI: 10.1149/2162-8777/abd48d
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ga2O3 Films Grown on m- and r-plane Sapphire Substrates by MOCVD

Abstract: Ga2O3 films were respectively deposited on m- and r-plane sapphire substrates by LP-MOCVD. The growth pressure greatly influenced the surface morphology and the grain shape, and the grain size obviously decreased with the increasing growth pressure. XRD results indicated that a higher growth pressure helped to suppress the polycrystalline orientation of β-Ga2O3 films grown on m-plane sapphire substrates, but was not conducive to the formation of α-Ga2O3. Ellipsometer measurement shows that the higher growth pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…6,15,26 In our previous work, we deposited and investigated a series of Ga 2 O 3 films on different substrates. We analyzed the influence of growth temperature or growth pressure on the crystal phase and orientation of Ga 2 O 3 films deposited on m− or r-plane sapphire substrates, 27,28 and found that the increase in growth pressure can supress the growth rate and grain size of β-Ga 2 O 3 films on sapphire substrate. 29,30 We also investigated the Ga 2 O 3 films deposited on the epi-GaN/sapphire substrates, and it still grew preferentially along the (−201) crystal plane family at higher growth temperatures.…”
mentioning
confidence: 99%
“…6,15,26 In our previous work, we deposited and investigated a series of Ga 2 O 3 films on different substrates. We analyzed the influence of growth temperature or growth pressure on the crystal phase and orientation of Ga 2 O 3 films deposited on m− or r-plane sapphire substrates, 27,28 and found that the increase in growth pressure can supress the growth rate and grain size of β-Ga 2 O 3 films on sapphire substrate. 29,30 We also investigated the Ga 2 O 3 films deposited on the epi-GaN/sapphire substrates, and it still grew preferentially along the (−201) crystal plane family at higher growth temperatures.…”
mentioning
confidence: 99%